THE ROLE OF DIGITAL MARKETING STRATEGY MEDIATES THE INFLUENCE OF DIGITAL ORIENTATION ON SUSTAINABLE BUSINESS PERFORMANCE - Putu Laksmita Dewi Rahmayanti; I Wayan Suartina; Ni Nyoman Kerti Yasa; I Gusti Ayu Tirtayani (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
This study aims to examine and explain the role of digital marketing strategy in mediating the effect of digital Orientation on sustainable business performance. The population of this study is Endek MSMES business actors in Bali who have adopted digital strategies within the last three years. The sample size used was 65 people using the purposive sampling method. The analysis technique used is Path Analysis using SEM- PLS. The results showed that digital Orientation affects sustainable business performance, digital Orientation affects digital marketing strategy, and digital marketing strategy also affects sustainable business performance. Digital marketing strategy can partially mediate the effect of digital Orientation on sustainable business performance. Therefore, endek MSME need to pay attention and increase the intensity of adopting digital marketing strategies to improve sustainable business performance.